Selective Synthesis of Glycerol Monostearate by Glycerol Borate - Kyong Il Choe; Chol Min Ri; Jong Nam Kim; Rak Won Paek (UPT Laboratorium Terpadu, Universitas Diponegoro, 2026)
Glycerol monostearate, a widely used nonionic surfactant in food, pharmaceutical, and cosmetic industries. However, current synthesis methods such as molecular distillation and functional group protection suffer from high equipment costs, complex post-processing, or low product purity. In this study, a boric acid ester protection method was developed to selectively synthesize high-purity glycerol monostearate. Quantum chemical calculations (AM1 method) and Monte Carlo simulations were used to predict optimal reaction conditions. Bisglyceride borate was synthesized and characterized by FT-IR, then esterified with stearic acid, and hydrolyzed to yield the final product. The optimal conditions were: glycerol-to-boric acid molar ratio 2:1, 115 °C with toluene as azeotropic agent, 70 min (bisglyceride borate conversion: 96.0%). The final product purity was >95% by HPLC, with melting point 61–63 °C and HLB value 3.8. This method offers mild conditions, simple post-processing, and high purity, making it industrially promising. Copyright © 2026 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).